PENGARUH PERSEPSI MANFAAT , PERSEPSI KEMUDAHAN ,SIKAP, KONTROL PRILAKU , DAN NORMA SUBYEKTIF TERHADAP MINAT PENGGUNAAN UANG ELEKTRONIK PADA BANK BUMN DI KOTA PEKANBARU - Karnadi, Zachrie; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to investigate the perception of interest in the use ofelectronic money in the city of Pekanbaru. This thesis analyzes the factors thatinfluence intention to use the use of electronic money as a new product categoryfor payment instrument in Indonesia, by raising electronic money case study at 3state-owned banks in Pekanbaru city. This research integrates Theory AcceptanceModel (TAM) and Theory Planned Behavior (TPB). This research is descriptiveand explorative quantitative research. Data acquisition conducted on customersand non-customers 3 BUMN Bank (Bank Mandiri, BRI, and BNI) This study foundthat intention to use the use of electronic money is influenced by perceiveduselfulness, attitude, perceived behavior control, and subjective norms.